2008
DOI: 10.1002/jmv.21152
|View full text |Cite
|
Sign up to set email alerts
|

Expression levels of MDR1, MRP1, MRP4, and MRP5 in peripheral blood mononuclear cells from HIV infected patients failing antiretroviral therapy

Abstract: The aim of the study was to evaluate the mRNA expression of four relevant ABC-transporter genes [MDR1 (P-glycoprotein; Pgp), MRP1, MRP4, and MRP5] in HIV-positive individuals failing treatment and analyze the association between the levels of their expression and viral load, CD4 cell count, and therapeutic history. Ninety-eight HIV-positive samples and 20 samples from healthy donors were analyzed, retrospectively. Peripheral blood mononuclear cells (PBMCs) from HIV1-positive individuals were collected at the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 35 publications
2
30
1
Order By: Relevance
“…This efflux transporter is widely distributed and has significant expression levels in the small intestine, liver, kidneys, and brain (Ho and Kim, 2005). It is also expressed in other tissues, such as the placenta, ovaries, testicles, and lymphocytes (Thiebaut et al, 1987;Cordon-Cardo et al, 1989;Klimecki et al, 1994;Turriziani et al, 2008). ABCB1 expression in lymphocytes has been observed in 20 to 80% of B lymphocytes and 30 to 80% of T cells (Chaudhary et al, 1992;Drach et al, 1992;Klimecki et al, 1994;Ludescher et al, 1998;Köck et al, 2007).…”
Section: G Atp-binding Cassette Subfamily B Member 1 Transporter (P-mentioning
confidence: 99%
See 1 more Smart Citation
“…This efflux transporter is widely distributed and has significant expression levels in the small intestine, liver, kidneys, and brain (Ho and Kim, 2005). It is also expressed in other tissues, such as the placenta, ovaries, testicles, and lymphocytes (Thiebaut et al, 1987;Cordon-Cardo et al, 1989;Klimecki et al, 1994;Turriziani et al, 2008). ABCB1 expression in lymphocytes has been observed in 20 to 80% of B lymphocytes and 30 to 80% of T cells (Chaudhary et al, 1992;Drach et al, 1992;Klimecki et al, 1994;Ludescher et al, 1998;Köck et al, 2007).…”
Section: G Atp-binding Cassette Subfamily B Member 1 Transporter (P-mentioning
confidence: 99%
“…It has been reported that ABCC1 and ABCC2 transporter expression was higher in CD4 ϩ cells, followed by CD8 ϩ and CD19 ϩ cells (Oselin et al, 2003). Briefly stated, mRNA or the protein was detected for the various ABCC1, -2, -4, and -5 transporters in monocytes, CD4 ϩ cell lines, and the lymphocytes of patients infected with HIV (Oselin et al, 2003;Zhang et al, 2006;Turriziani et al, 2008;Weiss et al, 2009).…”
Section: H Atp-binding Cassette Subfamily C Transporters (Multidrug mentioning
confidence: 99%
“…MRP4 is widely expressed in a range of human blood cells including CD34 ? stem cells, erythrocytes, platelets, granulocytes and lymphocytes [24,25]. MRP4 is localized in the plasma membrane and shows an ATPdependent transport of a broad range of compounds.…”
Section: Introductionmentioning
confidence: 99%
“…We have two main reasons to pursue these aims: first, it has been shown that MDR1 locus has recently undergone positive selection, most likely due to environmental factors, which may include xenobiotics and pathogens (Tang et al, 2004; Wang et al, 2007). Although, to our knowledge, no report has indicated genetic changes in MDR1 associated with HIV, HIV-infected patients showed a significant increase in P-gp expression in CD4 + and CD8 + T cells (Andreana et al, 1996), in MDR1 mRNA levels and P-gp expression in placentas (Camus et al, 2006), and in MDR1 mRNA levels in peripheral blood mononuclear cells (PBMCs) (Turriziani et al, 2008). In this study, we sought to determine whether MDR1 genetic characteristics are similar or different between HIV-positive and HIV-negative individuals.…”
Section: Introductionmentioning
confidence: 99%